The efficacy of photodynamic therapy for herpes simplex lesions in immunocompetent and oncologic individuals - Mello, Fernanda W; Mariani, Taimara; Lisboa, Mariah L; Durigon, Giovanna S; Camargo, Alessandra R; Munhoz, Etiene A (Journal of Oral Diagnosis, 2022)
Aims: To investigate the efficacy of antibacterial photodynamic therapy (APDT) for the treatment of herpes simplex oral and perioral lesions in immunocompetent and oncologic individuals. Methods and Results: APDT was applied in G1 (immunocompetent, n=26) and G3 (oncologic, n=6) with methylene blue 0.01% followed by 660ηm low level LASER in all the lesion area. In G2, immunocompetent patients received Acyclovir cream 50mg/g prescription. Lesion stage, size, edema, and pain degree were obtained at the beginning of the treatment (T0), after 24 hours (T1), 48 hours (T2), 72 hours (T3), and 7 days (T4). Intra-group analyses showed significant improvement in all criteria for G1 and G3 between T0 and T4 (p<0.05), while for G2 no differences were found in lesion stage and pain level between study times (p>0.05). Most of G1 individuals showed crust stage in T2 and T3, while most of G3 individuals presented papule or vesicle at the same times (p<0.05); and G2 presented higher scores of edema in T2 than G1 and G3 at the same time (p<0.05). Conclusions: It is possible to conclude that APDT is an effective adjuvant treatment for HSV oral and perioral infections in both immunocompetent and oncologic individuals.